First Report of Neofusicoccum parvum Causing Leaf Spot on Geodorum eulophioides in China - Du, Chan Juan (Plant disease, 2020)
Geodorum eulophioides Schltr. is a critically endangered orchid listed in the International Union for Conservation of Nature (IUCN) Red List of threatened species. At present, only two natural populations were found in China. It has important scientific and ornamental values because of its uniqueness. During the summer of 2019, a black leaf spot disease occurred on G. eulophioides, in Yachang Orchid National Nature Reserve (E106°13'32″，N24°44'19″) in Guangxi province, China. More than 60% of leaves of these plants were infected. The disease symptoms initially appeared as small yellow circular spots, which enlarged into irregular brown spots (6 to 9 cm length and 3 to 5 cm width). In later stages of the disease development, the center of the spots became dark brown with a clear edge and surrounded by a yellow halo. In severe infections, the spots coalesced covering the entire leaf. Six symptomatic leaves were collected from three infected plants, surface sterilized in 75% ethanol for 15 s and 0.1% HgCl2 for 4 min, and subsequently washed three times with sterile water, then plated onto potato dextrose agar (PDA), and incubated at 28℃ for three days. Eighteen fungal cultures with similar morphological characteristics were obtained from the infected tissues. Colonies were initially white, then turned dark grey after nine days. To induce sporulation, isolates were grown on 2% water agar and incubated under UVA light at 28℃ for nine days. Three isolates were selected for morphological characterization. Conidia were hyaline, unicellular, nonseptate, ellipsoidal to fusiform, externally smooth, thin-walled, and ranged from 10.7 to 16.6 μm (avg. 13.8 μm) × 4.1 to 6.7 μm (avg. 5.1 μm) (n=50). The isolate DBL-1 was selected as a representative for molecular identification. Genomic DNA was extracted and used for PCR to amplify the rDNA internal transcribed spacer region (ITS), translation elongation factor 1-alpha gene (EF1-α), and beta-tubulin gene (TUB2), using the primer pairs ITS1/ITS4 (White et al., 1990), EF1-728F/EF1-986R（Alves et al. 2008；Carbone & Kohn, 1999）, and T1/T2 (O'Donnell et al., 1997), respectively. The obtained ITS sequence (GenBank Accession No. MN918440), EF1-α sequence (MN963815), and TUB2 sequence (MN963816) showed >99% homology with several GenBank sequences of Neofusicoccum parvum (JX513636, KU997497 for ITS, KU997261, MH252401 for EF1-α, and KJ841779, MK412882 for TUB2, respectively). Based on morphological characteristics of the asexual morph and maximum likelihood analyses of a combined rDNA-ITS, EF1-α and TUB2 gene sequences, was identified as N. parvum. Pathogenicity test was performed using isolate DBL-1 by inoculating 3 leaves of G. eulophioides plants. The test was repeated three times. Each leaf was wounded using a sterile needle, and a mycelial plug (6 mm diameter) harvested from the periphery of a 3-day-old colony grown on PDA was placed on each wound. Plants were then covered with plastic bags to maintain high relative humidity of 90% and kept at 28℃ in a greenhouse under natural daylight conditions. An equal number of leaves on the same plant were inoculated using sterile PDA plugs and served as mock inoculated controls. After three days, all the inoculated leaves showed black spot symptoms resembling those observed in the field, whereas controls remained symptomless. The fungus was re-isolated from the symptomatic leaves, thus completing Koch's postulates. N. parvum has been reported to cause leaf spot disease on Myristica fragrans (Jayakumar, et al., 2011), Ginkgo biloba (Mirhosseini, et al., 2014), Vitis heyneana (Wu, et al., 2015), and Hevea brasiliensis (Liu et al., 2017), respectively. To the best of our knowledge, this is the first report of N. parvum causing leaf spot disease on G. eulophioides in China. The disease control measures and in-situ conservation method need to be strengthened to protect this rare species